Porcine innate antiviral immunity: host defense peptides and toll-like receptors - Sang, Yongming (Kansas State University, 2008)
The immediate antiviral defense residing in the innate immune system of multicellular organisms critically determines the outcome of viral infection. This dissertation presents a study of the "effectors" and "receptors" of porcine innate immunity in infection caused by porcine reproductive and respiratory syndrome virus (PRRSV), which is the most devastating pathogen impacting the swine industry. In the first investigation, eleven novel porcine host defense peptides (HDPs), [Beta]-defensins (pBDs), were identified and characterized. All of these peptides have a consensus [Beta]-defensin motif and phylogenetically are similar to orthologs from other species. A differential expression pattern for these 11 newly identified genes was found. For example, pBD-2 and pBD-3 were expressed in bone marrow, lung, skin and other lymphoid tissues. pBD-2 and pBD-3 were further characterized for their gene structure, and antimicrobial activity of synthetic peptides. The second study was conducted to evaluate PRRSV-induced differential expression of porcine HDPs and direct antiviral activity of selected HDPs against PRRSV. In vitro incubation of PRRSV with synthetic pBD-3 or protegrin-4 (PG-4) significantly inhibited viral infectivity. Using nine protegrin-derived peptides, it was determined that cyclization of PG-4 increased anti-PRRSV activity and mutation of some residues in PG-4 diminished some of the activity. These findings suggest the potential role of porcine HDPs as a group of innate antiviral effectors. In the third and fourth investigations, porcine Toll-like receptor (TLR) 3 and TLR7 were identified and functionally expressed. Increased expression of TLR3 was observed in PRRSV-infected porcine lungs. Stimulation of porcine alovelar macrophages with poly (I:C), a synthetic TLR3 ligand, increased expression of interferon-[Beta] and suppressed PRRSV infectivity. Activation of porcine TLR3 overexpressed in a PRRSV-sensitive cell line, elicited antiviral responses to PRRSV infection. Partial silencing of TLR3 in PAMs resulted in increased PRRSV infection. In summary, these data provide molecular information on porcine TLR3 and TLR7, and their involvement in PRRSV pathogenesis, which may elicit new strategies to prevent this costly swine disease.
Keywords: Innate antiviral immunity; Host defense peptides; Toll-like receptors; PRRSV; Biology, Molecular (0307); Biology, Veterinary Science (0778); Health Sciences, Immunology (0982)